(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Nurturing a personal culture in the learning process is defined as a strategic task of higher education. At the same time, the formation of an individual’s culture of thinking as the basis of his general culture is a prerequisite for the comprehensive development of the individual.